Perbandingan Pelindungan Indikasi Geografis di Indonesia dan Malaysia - Indra Hendrawan; Dimas Yanuarsyah; Atik Winanti (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
One of the special aspects of Intellectual Property (IP) is Economic Rights, namely the right to obtain economic benefits from intellectual property. The creation of economic value shows that IP is one of the objects of trade that plays an important role in the development of a nation. As part of Intellectual Property, Geographical Indications are a trading tool that can provide benefits for producers, consumers, and the community in identifying products and providing quality assurance, avoiding fraudulent practices, helping the development of local producers, and supporting the preservation of nature and traditional knowledge. To carry out optimal IPR protection, a comparison needs to be made with practices that have been running so far, in this case a comparison will be made with practices in Malaysia. This research method uses a descriptive qualitative approach by collecting data from various sources. This research will use a conceptual/theoretical approach and a comparative approach. This research will determine the country's strategy to protect intellectual property in Indonesia and Malaysia and determine an effective model in protecting Geographical Indications. Thus, this research produces a deep understanding of the protection of Geographical Indications, highlighting the successes and challenges in increasing success related to intellectual property.